Risk Factors for Cervical Cancer Incidence at Ibnu Sina Hospital Makassar - Nadhifah Khairun (Fakumi Medical Journal: Jurnal Mahasiswa Kedokteran, 2023)
Cervical cancer is a malignant tumor that occurs in the cervical region at the end of the cervix. Based on data from the International Agency for Research on Cancer (IARC), it is known that the second highest cause of death is cervical cancer, reaching 460,000 cases and 230,000 women deaths. Cervical cancer is caused by HPV infection and several factors, namely age, parity, age of first sexual intercourse, number of sexual partners history, HPV vaccination history, smoking history, and oral contraceptives history. To determine the risk factors for cervical cancer incidence at Ibnu Sina Hospital Makassar. This was descriptive retrospective study method. With cross sectional research design. The total sample was 68 people with cervical cancer at Ibnu Sina Hospital Makassar. The distribution of age 30-60 years (85.3%), parity >3 (57.4%), and age of first sexual intercourse >17 years (85.3%). There was no history of using oral contraceptives (54.4%), HPV vaccination history (97.1%), and smoking history (98.5%). Having only 1 history of number of sexual partners (89.7%), employment history was not out of town (63.2%), and the most common type of cervical cancer was squamous cell carcinoma (76.5%). The distribution of risk factors for the incidence of Cervical Cancer at Ibnu Sina Hospital was mostly found at the age of 30-60 years, parity> 3, age of first sexual intercourse >17 years, no history of using oral contraceptives, no HPV vaccination history, no smoking history, having 1 history of sexual partners, work history not out of town, and the type of cervical cancer is squamous cell carcinoma.